MENGHITUNG EFISIENSI THERMAL PADA ALAT VERTICAL RAW MILL DI PABRIK BATURAJA II PT SEMEN BATURAJA (PERSERO) TBK. - Alfiansyah Miftahul Rizky; Anugrah, Rendotian; Safaruddin, Safaruddin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
In the process of making cement at PT Semen Baturaja (Persero) Tbk. There are seven processes that occur, namely the mining process (quarry), the grinding process (crushing) and drying (drying), the raw meal burning process into clinker, clinker cooling, clinker grinding, and the packing process. The vertical raw mill is the main tool used in the process of grinding and drying raw materials using a drying medium, namely hot air from kiln exhaust gases. In this milling and drying process, limestone, clay, silica sand and iron sand, will produce a product, namely raw meal. In order for the reactivity of the material to be achieved in the next process, the standard of fineness of raw meal must have a sieving above 90µ (14-20%). In the drying process, the raw mill can dry materials that have a moisture content of 15% to <1%. The maximum moisture content is permitted at 1%, this is important to anticipate possible obstacles in transportation and to improve thermal efficiency. Efficiency is a measure in comparing a process of using input energy with the realized use or output of a process of activities carried out as well as the sources and energy used. In vertical raw mill equipment, thermal efficiency needs to be calculated to determine whether the quality of the heat used is maximal, where in the vertical raw mill the standard thermal efficiency value has been set in the range of 85 - 100%. In the results and discussion, the highest thermal efficiency value on the vertical raw mill tool is 96.28% with a heat loss value of 3.71%, while the lowest thermal efficiency value obtained is 87.90% with a heat loss value of 12.09%. For the heat balance, the highest total vertical raw mill heat balance is 33,922,195.16 kcal and the lowest is 22,506,739.34 kcal.